ANALISIS MODEL PREDIKSI PEMERINGKATAN OBLIGASI SYARIAH PERUSAHAAN DENGAN PENDEKATAN RASIO KEUANGAN DI BURSA EFEK INDONESIA - Karima Tamara (IAIN Pekalongan, 2013)
This study aimed to determine whether financial ratio was a predictor to predict future bond ratings, and which one was significant. This study concentrates on techniques to predict bond ratings. Bond rating is important because these rankings provide an informative statement and provide a signal about the probability of default of a company's debt. The Islamic bond companies listed in Indonesia Stock Exchange (IDX) and assessed by rating agencies PEFINDO in 2009- 2011 were used to answer the research question. Leverage (LTLTA), liquidity (CaCl), solvency (CFOTL), profitability (OIS), and productivity (STA) were used as variable of financial ratio. This study examined the financial ratios that can establish sharia bond rating prediction model using discriminant analysis (MDA). The results were : (1) there were different level of Islamic bond in financial ratios of liquidity (CaCl), solvency (CFOTL), profitability (OIS), and productivity (STA); (2) financial ratios, that could form the prediction model of Islamic bonds ranking, were CaCl , OIS , STA, (3) the accuracy level of the formed model were 94.3%.